Price, product quality, and brand image as antecedents of customer satisfaction - Aulia, Rina; Adhilla, Fitroh; Yusoff, Rushami Zien (Journal of Management and Business Insight, 2024)
Purpose- Technology is one of the most essential things in human life. The advancement and development of technology, especially communication technology, cause every telecommunications company to continue improving its products' excellence to keep up with technological developments. This study aims to determine the effect of price, product quality, and brand image on consumer satisfaction of iPhone Smartphone users in Yogyakarta, Indonesia. Design/Methodology/Approach- The study subjects were people in Yogyakarta, Indonesia, with a sample size of 100 people selected using a purposive sampling technique. This research uses a quantitative approach and data collection techniques, such as distributing questionnaires. Instrument tests were carried out with measurement models, validity tests, reliability tests, and structural model testing through bootstrapping. The analytical tool used in this research was Smart PLS 3.0. Findings- The study's findings show that consumer satisfaction is positively impacted by price, product quality, and brand image. Customers are satisfied when the price is determined according to the demands or advantages they want. Customer satisfaction will be determined by the product's quality. Furthermore, the brand image will give an impression of a product. When using or buying a product, consumers will choose products with a familiar brand image because it will give the assumption that a positive brand image will provide consumers with a feeling of satisfaction. Research limitations/implications- The limitation of this research is the process of collecting data from respondents, which takes quite a long time. The distribution of online questionnaires was only addressed to respondents who used iPhone Smartphones in Yogyakarta, so the respondents' answers could not represent all Smartphone users of various brands in Yogyakarta, Indonesia. Originality/value- There is still little research on the antecedents that cause consumers to use iPhone smartphones, especially in Yogyakarta. Similar studies only discuss Smartphone users in general in Yogyakarta or iPhone Smartphone users in several regions in Indonesia.